Notes clarifying the status on some ethnobotanical species from the Ecuadorian Amazon - Luzuriaga-Quichimbo, Carmen X.; Escobar García, Pedro; Cerón-Martínez, Carlos E.; Blanco-Salas, José; Ruiz-Téllez, Trinidad (Mediterranean Botany, 2019)
Despite belonging to one of the most biodiverse ecoregions on Earth, the Ecuadorian Amazon remains largely unexplored. During the elaboration of an ethnobotanical checklist of the useful plants in the Kichwa community of Pakayaku (Pastaza, Ecuador), we faced taxonomical difficulties due to the lack of basic information and unknown location of type specimens for several plant names. In this contribution, we present notes clarifying the status of six taxa of the H. Karsten and E. F. Poeppig names and locate the corresponding type specimens at the herbarium W (Natural History Museum, Vienna).